Pengaruh Konsentrasi Kitosan Terhadap Karakteristik Bioplastik Selulosa Batang Pisang dengan Plasticizer Gliserol - oktavia, oktavia; Puspita, Indah; Kusmita, Tri; Utami, Rizka (Jurusan Fisika, Universitas Bangka Belitung, 2025)
The development of bioplastics has continued to grow as an alternative material based on renewable natural resources. Cellulose is a natural polymer that is widely used as a raw material for bioplastics; however, cellulose-based bioplastics generally show limited mechanical stability and rigidity. Therefore, the addition of chitosan and glycerol is required to improve their characteristics. This study aims to determine the cellulose content and functional groups of banana stem cellulose and to analyze the effect of chitosan concentration on the thickness, mechanical properties, and degradation rate of banana stem cellulose-based bioplastics using glycerol as a plasticizer. Bioplastics were synthesized by varying the chitosan concentration at 1%, 2%, 3%, and 4%. The results showed that the cellulose content of banana stems reached 93%, with the presence of –OH, –CH, and –CO functional groups. The variation in chitosan concentration affected the thickness, tensile strength, elongation at break, and degradation rate of the bioplastics. An increase in chitosan concentration resulted in a decrease in thickness and elongation, while tensile strength and degradation rate increased with higher chitosan content. These results indicate that chitosan concentration significantly influences the physical, mechanical, and degradation properties of banana stem cellulose-based bioplastics, demonstrating their potential as biodegradable materials.